Divja odlagališča odpadkov na območju Ljubljane - Smrekar, Aleš (Georitem, 2007)
Studies to date on illegal waste dumps in the Ljubljana Plain (Ljubljansko polje), the Iška Alluvial Fan (Iški vršaj), and areas with local water sources in the City of Ljubljana have demonstrated that there are great amounts of waste in areas of importance to the Slovenian capital's water supply. In particular, illegal dumps located in areas where groundwater flows towards pumping stations and where the Sava and Iška rivers flow into the groundwater present a considerable threat to drinking water quality. In addition, shallow groundwater levels and gravel pits increase the vulnerability of the environment even more.